Pengaruh Ekstrak Metanol Daun Kayu Kuning (Arcangelisia flava (L.) Merr) terhadap Histopatologi Aorta Tikus Wistar Hiperlipidemia (The Influence of Methanol Extract of Yellow Root (Arcangelisia flava (L.) Merr) Leaves on Aortic Histopathology in Hyperli - Yuniar Wahyu Rahmawati; Evi Umayah Ulfa; Ema Rachmawati (Pustaka Kesehatan, 2016)
Atherosclerosis is the leading cause of heart attack and stroke. Hyperlipidemia is one of the triggers of atherosclerosis through oxidative stress and formation of foam cells. Atherogenic index (the ratio of LDL/HDL) is a predictive parameter of coronary heart disease. A.flava is potential as antiaterosklerosis due to the content of berberine and flavonoids. This study was undertaken to determine the ability of methanolic extract of A.flava leaves (EMDAf) in lowering atherogenic index and the number of foam cells. Five groups experimental animals (each consisting of 4 rats) was induced with high fat and fructose diet for 45 days, followed by administration of EMDAf dose of 250 mg/kg BW, 500 mg/kg BW, 750 mg/kg BW, simvastatin 1.8 mg/kg BW (control (+)), and CMC Na 1% (control (-)) for 7 days treatments. Then the rat arcus aorta was taken for histopathological examination with Masson Trichrome staining. ANOVA test results showed that EMDAf could decrease the atherogenic index, but not significantly (p> 0.05). While the Kruskall Wallis test results showed that the increase dose of EMDAf might improve histopathology of the aorta through a reduction in the number of foam cells significantly compared to the negative control (p <0.05). Berberine contents in EMDAf is 0.046% measured by TLC-densitometry. It could be concluded that methanolic extract of A.flava leaves had the ability to decrease in the atherogenic index value and the number of foam cells.   Keywords: Arcangelisia flava leaves, foam cells, atherogenic index, aorta, histopathology